A systematic review of sustainable supply chain management in global supply chains. (10th January 2019) - Koberg, Esteban; Longoni, Annachiara
Abstract: Recurring controversies involving supply chain-related sustainability incidents suggest that firms with a global presence struggle to improve environmental, social and economic outcomes in global supply chains. Sustainable supply chain management has been suggested for improving sustainability outcomes in supply chains, yet global supply chains pose unique challenges. This paper aims to provide a synthesis of the key elements of sustainable supply chain management in global supply chains. To achieve this goal, we conduct a rigorous systematic literature review of articles focused on sustainable supply chain management in global supply chains and apply structured content analysis to * mentioned articles spanning 15 years of research published in English-language, peer-reviewed journals. The research contributes by identifying configurations and governance mechanisms as key elements characterizing sustainable supply chain management in global supply chains and synthesizing their relationship with sustainability outcomes. Overall configurations characterized by a greater connection between the focal firm and multi-tier suppliers, managed directly or through third parties, are increasing trends suggested to better serve sustainability development and offer several areas for future research. The research also contributes to practice by providing managers of focal firms with global supply chains directions for improving sustainable outcomes in their supply chains. Highlights: Systematic review of sustainable supply chain management in global supply chains. Key elements of SSCM in global supply chains identified. SSCM configurations and SSCM governance mechanisms are analyzed. Outcomes along environmental, social and economic dimensions are analyzed. Gaps in literature are identified and future research directions are proposed.